Membangun Jembatan Kesadaran Multiiman: Sebuah Proposal Visioner dari Greja Kristen Jawi Wetan - Hardiyan Triasmoroadi (Societas Dei: Jurnal Agama dan Masyarakat, 2023)
In the face of religious tensions within the Indonesian context, the East Java Christian Church grapples with the imperative question: "How can the church effectively engage with a multifaith world amidst religious and social tensions?" In response to the question, I contend that the church can build its multifaith awareness by adopting a model derived from Javanese tradition, namely jagongan and patuwen, Jagongan embodies communal characteristics, while patuwen signifies personal and private qualities. These Javanese traditions mirror the twofold movement of Jesus—exitus a Deo and exitus a se—reflecting both exit from Father and of Himself leading to a return and entry to the Divine. The church can engage jagongan as an invitation for people to enter and gather in public space and employ patuwen to reach out and exit from the church space to embrace people's private space. I will demonstrate the practical implementation of jagongan and patuwen as spaces for multifaith learning and social justice awareness within the church, presented under the banner of the Festival of Faith. In conclusion, jagongan and patuwen emerge as powerful models for bridging and enriching the church's multifaith awareness, fostering greater understanding, inclusivity, and social justice in the diverse landscape of faith.